Post-Traumatic Stress Disorder of Participants in Military Action: the Problem of Human Rights Ensuring - Чернишов, Георгій Михайлович; Чернишов, Г. М.; Чернышов, Георгий Михайлович; Chernyshov, Heorhii M. (Los Hemisferios University, 2020)
The article is devoted to the study of the problem of post-traumatic stress disorder (PTSD) of combats in the context of the protection of human rights.Methods used in this research are theoretical and empirical, with an anonymous survey of 212 participants in the fighting in the East of Ukraine. Attention is focused on the fact that PTSD is a complex problem, the negative consequences of which are studied in the framework of sociology, criminology, and criminal proceedings, as well as psychology, psychiatry, medicine in general. The article discusses the features of post-traumatic stress disorder of combats in the east of Ukraine. The conclusions are formulated on the main social problems of war veterans in Ukraine and ways to solve them. It has been established that persons who took part in hostilities in the east of Ukraine have a number of social problems after returning from the conflict zone, because of which individuals cannot fully exercise their constitutional rights. A potential “risk group”is defined in the article among war veterans who are in greater need of social and governmental patronage. In addition, it formulates specific proposals to minimize the possible negative consequences of participation in hostilities, as well as to protect constitutional rights, establish social policies and support war veterans.

Стаття присвячена дослідженню проблеми посттравматичного стресового розладу (ПТСР) бійців в контексті захисту прав людини. Методи, використані в цьому дослідженні, є теоретичними та емпіричними, з анонімним опитуванням 212 учасників бойових дій на Сході України. Акцентується увага на тому, що ПТСР є складною проблемою, негативні наслідки якої вивчаються в рамках соціології, кримінології та кримінального провадження, а також психології, психіатрії, медицини загалом. У статті розглядаються особливості посттравматичного стресового розладу бійців на Сході України. Сформульовано висновки щодо основних соціальних проблем ветеранів війни в Україні та шляхів їх вирішення. Встановлено, що особи, які брали участь у бойових діях на Сході України, мають ряд соціальних проблем після повернення із зони конфлікту, через що особи не можуть повною мірою реалізовувати свої конституційні права. У статті визначено потенційну “групу ризику” серед ветеранів війни, які більше потребують соціального та державного патронату. Крім того, формулюються конкретні пропозиції щодо мінімізації можливих негативних наслідків участі у бойових діях, а також для захисту конституційних прав, встановлення соціальної політики та підтримки ветеранів війни.

Статья посвящена исследованию проблемы посттравматического стрессового расстройства (ПТСР) бойцов в контексте защиты прав человека. Методы, использованные в этом исследовании, являются теоретическими и эмпирическими, с анонимным опросом 212 участников боевых действий на Востоке Украины. Акцентируется внимание на том, что ПТСР является сложной проблемой, негативные последствия которой изучаются в рамках социологии, криминологии и уголовного производства, а также психологии, психиатрии, медицины в целом. В статье рассматриваются особенности посттравматического стрессового расстройства бойцов на Востоке Украины. Сформулированы выводы относительно основных социальных проблем ветеранов войны в Украине и путей их решения. Установлено, что лица, принимавшие участие в боевых действиях на Востоке Украины, имеют ряд социальных проблем после возвращения из зоны конфликта, из-за чего лица не могут в полной мере реализовывать свои конституционные права. В статье определено потенциальную «группу риска» среди ветеранов войны, которые больше нуждаются в социальном и государственном патронате. Кроме того, формулируются конкретные предложения по минимизации возможных негативных последствий участия в боевых действиях, а также для защиты конституционных прав, установления социальной политики и поддержки ветеранов войны.
Chernyshov H. Post-Traumatic Stress Disorder of Participants in Military Action: the Problem of Human Rights Ensuring / H. Chernyshov // Ius Humani. Law Journal. – V. 9 (1). – Los Hemisferios University, 2020. – P. 61-86.
Keywords: Post-Traumatic Stress Disorder (PTSD); War Veterans; Armed Conflict; Human Rights; Protection of the Rights of Veterans; посттравматичний стресовий розлад (ПТСР); ветерани війни; збройні конфлікти; права людини; захист прав ветеранів; посттравматическое стрессовое расстройство (ПТСР); ветераны войны; вооруженные конфликты; права человека; защита прав ветеранов; Research Subject Categories::LAW/JURISPRUDENCE